Do state-owned participation shareholders improve the environmental governance level of private enterprises? Evidence from Chinese listed firms - Zou, Ling; Ma, Jiejing (Frontiers in Environmental Science, 2023)
In recent years, whether the mixed-ownership reform system of introducing state-owned participation shareholders into private enterprises helps to improve the environmental governance of private enterprises has been a matter of much attention and discussion. Based on data from 2007-2019 for Chinese A-share private listed companies, this paper examines how the state-owned participation shareholders affect the environmental governance level of private enterprises. The results show that state-owned participating shareholder participation will significantly improve the environmental governance level of private enterprises, and this phenomenon is more significant among industrial enterprises and enterprises in regions with a higher degree of marketization. Furthermore, there is a substitution effect between state-owned participation shareholders, the executive team’s participation in politics, and Party organization establishment in improving the environmental governance level of enterprises, and the role played by state-owned participation shareholders is much larger than that played by the executive team’s participant in politics and Party organization establishment. In addition, the supervision effect is better when state-owned participation shareholders are from the local area and have a higher level of participation.